First zone algorithm for protection of series compensated lines. - Saha, M.M.
This paper presents a new first zone algorithm for distance protection of series compensated lines. The algorithm detects faults with the reach of 75-85% of the line length by measuring two distinctive impedances, using three adequate regions on the impedance plane and applying appropriate logic functions. The algorithm estimates instantaneous values of the voltage drop across the series capacitors online, and compensates for this signal when calculating the impedance valid for faults behind the series capacitors. The other impedance (without compensation) is calculated for faults in front of the series capacitors. An explicit selecting procedure for the two impedances is not required since the presented relaying method asserts directly the fault within or outside the first zone. The algorithm is presented in detail and extensively tested using the EMTP model of a 400 kV 300 km transmission line. The enclosed results demonstrate high speed, dependability and security of the new algorithm
Keywords: 300 km; 400 kV; EMTP model; Distance protection; Explicit selecting procedure; Fault detection; First zone algorithm; Impedance measurements; Impedance plane regions; Logic functions; Relaying method; Series capacitors; Series compensated power transmission lines protection; Voltage drop